Technical training: reality, demands and expectations of educational institutions of the secondary level of Tacna-Perú - Mazuelos Soldevilla, Percy Dario (2023)
In recent years, the Ministry of Education has been implementing sectoral strategies in order to promote technical training in cycles VI and VII of Regular Basic Education and thus ensure that secondary school students develop skills and abilities to entrepreneurship. The objective of this study was to know the situational status of the use of digital tools and their teaching support, in educational institutions belonging to the Regional Sectoral Directorate of Education of Tacna (Peru), which offer technical training in the curricular area of Education for the job. A basic research design was used, at an exploratory-descriptive level, and a mixed approach (quantitative and qualitative) was adopted. Among the findings, it is important to show that there is a significant relationship between the use of design programs and the entrepreneurial skills of students, being a relevant element for the development of future research related to technical training in secondary level educational institutions.